Does Fat Bingeing Increase Ethanol Consumption in Adolescents? - Marques, João (2020)
Evidence has been suggesting that neurochemical and behavioral adaptations emerging during one addictive behavior may enable a subsequent, different, addiction, even when the first one has ended. Such association seems remarkably accurate to fat bingeing and ethanol consumption, which constitute a relevant example of addictive patterns sequential association, particularly in adolescence. Therefore, the main purpose of the following review is to comprehend if adolescents who have engaged on fat bingeing escalated their ethanol consumption, after fat bingeing terminus, and secondly, in a positive scenario, to highlight why such association may happen. After searching databases such as MEDLINE (PubMed) and Clarivate Analytics Web of Science, all articles focused on adolescent humans or adolescent rats or adolescent mice, that included topics on fat bingeing and consequent ethanol consumption, were considered. Gathered results strengthened the referred hypothesis. Reports stating that adolescent fat bingers engage on escalated ethanol consumption were fundamentally supported by a prevalent fast food and ethanol cultures, bingers ‘shared personality traits, adolescence ‘susceptibilities for addictive behaviors and neurochemical and behavioral craving installment after fat bingeing cessation. Given that adolescence is a key structural and functional phase of human development, and that fat and ethanol consumption are linked to harmful physiological and social effects, priority must be given to multidisciplinary interventions aiming to challenge addictions, both pharmacologically and psychotherapeutically.